Accounting spreadsheet applications : using microsoft Excel - Malycha, Paul.; Pascoe, Ian. (South Melbourne : Nelson, 1996)
This book is about: Cash budget; Loan repayment schedule; Cash forecasting; Spreadsheet design; ...
Keywords: Accounting; Microsoft Excel; Microsoft Excel (Computer file) -- Problems, exercises, etc; Accounting -- Data processing; Electronic spreadsheets